A national survey of first line antibiotic use in neonatal units – and the potential scope for iatrogenic sensorineural hearing loss prevention - Peterson, J.; Muddiman, L.; Groves, F.; Booth, N.; Newman, W. G.; McDermott, J. H.; Mahaveer, A. (Frontiers in Pediatrics, 2024)
Objective National Institute for Clinical Excellence (NICE) guidance for the management of neonatal sepsis recommends a first-line antibiotic regimen containing an aminoglycoside (gentamicin). Aminoglycoside exposure causes sensorineural hearing loss in individuals with a specific mitochondrial genetic variant (m.1555A>G). This variant can be detected promptly (in <30minutes) by a point of care test. NICE does allow for variation in antibiotic regimes depending on local microbiology guidance. As practices can vary, this survey aimed to determine the current use of first-line antibiotic agents within neonatal units and postnatal wards across the UK.Design and setting A telephone survey was conducted across all neonatal units in the United Kingdom. Responses were requested from a member of the neonatal team experienced in neonatal septic screening processes. One response was recorded per unit.Of the 187 neonatal units, 186 (99%) responded to the survey. One unit declined to participate. The survey results show most neonatal units (93%) and postnatal wards (74%) across the United Kingdom use aminoglycosides as first-line antibiotic agents. Antibiotic regimes varied between different units and between different locations within the same hospital (NICU versus postnatal wards). In cases where there was a contraindication to aminoglycosides, the most common alternative antibiotic was cefotaxime.Conclusions Most neonatal units in the UK use an aminoglycoside antibiotic as firstline agent for suspected sepsis. This places infants with the m.1555A>G genetic variant at risk of iatrogenic hearing loss. There needs to be integration of point-of-care genetic testing within the neonatal septic screening pathway.